The Use of Etoricoxib and Celecoxib for Pain Prevention After Periodontal Surgery: A Double-Masked, Parallel-Group, Placebo-Controlled, Randomized Clinical Trial - Steffens, Joao Paulo; Santos, Fabio Andre; Pilatti, Gibson Luiz (Amer Acad Periodontology, 2011)
Background: Postoperative pain is an adverse effect of periodontal surgeries and may therefore be prevented or minimized. This study was conducted to evaluate the clinical efficacy of two selective cyclooxygenase-2 inhibitors, celecoxib and etoricoxib, on pain prevention after periodontal surgery.Methods: For this double-masked, parallel-group, placebo-controlled, and randomized clinical trial, 56 open-flap debridement surgeries were performed. The groups received three different protocols 1 hour before surgery: 1) 200 mg celecoxib (and another 200 mg 12 hours after the first dose); 2) 120 mg etoricoxib; or 3) placebo. Pain intensity and discomfort were assessed up to 2 days after surgery using the visual analog scale and the four-point verbal rating scale, respectively. Patients were instructed to take 750 mg acetaminophen as a rescue medication if necessary.Results: Pain intensity levels in the etoricoxib group were lower than in the placebo group at the 2-, 3-, 4-, 5-, 6-, and 7-hour periods after surgery (Kruskal-Wallis test; P < 0.05). There was no statistically significant difference between celecoxib and etoricoxib. Discomfort in the celecoxib group was significantly lower than in the placebo group only at the 3-hour period (P = 0.03). Rescue medication intake was significantly less frequent in the etoricoxib group than in the placebo and celecoxib groups (analysis of variance; P = 0.009).Conclusion: It was concluded that a single etoricoxib dose is not superior to two split doses of celecoxib when used for pain prevention after open-flap debridement surgery. J Periodontol 2011;82:1238-1244.
Keywords: Analgesia; celecoxib; etoricoxib; pain measurement; pain; postoperative; preanesthetic medication